1999
DOI: 10.1088/0953-8984/11/43/316
|View full text |Cite
|
Sign up to set email alerts
|

Construction of size-consistent effective Hamiltonians for systems with arbitrary Hilbert space

Abstract: Effective Hamiltonians are usually constructed by using canonical transformations or projection techniques. In contrast to this, we present a method for systems with arbitrary Hilbert space based on the introduction of cumulants. Cumulants guarantee size consistency, a property that is not always evident in other treatments. As a nontrivial example of use the derived method is applied to the strong-coupling limit of the half-filled Hubbard model on a general lattice in arbitrary spatial dimension for which the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 36 publications
(70 reference statements)
0
13
0
Order By: Relevance
“…28 However, a quantitative comparison cannot be made since in the experiment the ordering and, correspondingly, J eff , are traced as a function of temperature for given other system parameters while we investigate the ordering at T = 0 as a function of the extended Hubbard repulsion V. Our calculation also agrees well with the analytical results of Refs. 16 and 29, where it was shown that the exchange rapidly decreases with increasing V. Quantitatively, at V =3, C = 0 our results give J eff Ϸ 0.06 while perturbation theory 16,29 predicts J eff Ϸ 0.04. Moreover, for V = 1.3, C = 0.35, which give a lattice distortion close to the value observed experimentally (see Fig.…”
Section: Dynamic Propertiesmentioning
confidence: 54%
“…28 However, a quantitative comparison cannot be made since in the experiment the ordering and, correspondingly, J eff , are traced as a function of temperature for given other system parameters while we investigate the ordering at T = 0 as a function of the extended Hubbard repulsion V. Our calculation also agrees well with the analytical results of Refs. 16 and 29, where it was shown that the exchange rapidly decreases with increasing V. Quantitatively, at V =3, C = 0 our results give J eff Ϸ 0.06 while perturbation theory 16,29 predicts J eff Ϸ 0.04. Moreover, for V = 1.3, C = 0.35, which give a lattice distortion close to the value observed experimentally (see Fig.…”
Section: Dynamic Propertiesmentioning
confidence: 54%
“…An example for a degenerate unperturbed groundstate was discussed in Ref. 9. Note that the cumulant expression (4) is also closely related to an effective Hamiltonian which was derived by Takahashi.…”
Section: Discussionmentioning
confidence: 93%
“…9 This method is a projection approach and is based on the construction of effective Hamiltonians for low-energy properties. Besides the automatically preserved size consistency of extensive variables, this cumulant method offers compact expressions for the different orders of the perturbation theory.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations